Advances in the CRISPR/Cas9 Mediated Genome Editing: A Review: CRISPR/Cas9 Mediated Genome Editing - Nawaz, Mohsin; Iqbal, Muhammad Q.; Shoaib, Iqra; Ahmad, Sidra; Ullah, Farhat; Hussain, Adil (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
The primary long-lasting objective of biomedical researcher’s is the expansion of some superior and fruitful conducts in order to make some targeted alterations to the living cells genome. In modern times, a novel and up-to-date tool have emerged which is CRISPR-associated protein-9 nuclease (Cas9) from a bacteria Streptococcus pyogenes. This tool has gained a lot of focus and delivered a significant excitement. It has been sanctioned that the Biological Sciences have one of the best ever discoveries in the form of CRISPR-Cas9, which makes the integration of anticipated traits in eukaryotic cells very well-organized and easy. Furthermore, these traits have the potency of being target specific. They do not follow a random insertion of genes in the genome of any organism. This revolutionary technology is very user and environment friendly, easy to handle, and can be easily applicable in other offshoots of biology including, health, agriculture, genetic syndromes, and other microbial diseases. In this review, we will provide, brief insights on the history of CRISPR/Cas9 system from its discovery to the mechanism of action. The literature for this review has been obtained from accessible catalogs namely, PubMed, Science Direct, Google Scholar and Research gate. With this revolutionary technology, the modification, regulation and locating of genomic loci in cells of all organisms indeed is a remarkable development.